Anchorage effects of ligation and direct occlusion in orthodontics: A finite element analysis. (November 2022) - Bi, Shaoyang; Guo, Ziyuan; Zhang, Xizhong; Shi, Guangyu
Highlights: A smooth geometry including upper and lower teeth is constructed using PolyNURBS. Orthodontic process considering molars ligation and direct occlusion is simulated. Figure-of-eight ligature can disperse orthodontic forces on the posterior teeth. A tiny orthodontic tooth displacement could change direction of occlusal force. Abstract: Background and objective: During orthodontic treatment, the figure-of-eight ligature and the physiological occlusion play an important role in providing anchorage effects. However, their effects on reaction forces of tooth and stress state in periodontal ligament (PDL) have not been quantitatively evaluated yet. In this study, we presented a finite element analysis process for simulating posterior molar ligature and direct occlusion during orthodontics in order to quantitatively assess their anchorage effects. Methods: A high precision 3D biomechanical model containing upper and lower teeth, PDL, brackets and archwire was generated from the images of computed tomographic scan and sophisticated modelling procedures. The orthodontic treatment of closing the extraction gap was simulated via the finite element method to evaluate the biomechanical response of the molars under the conditions with or without ligation. The simulations were divided into experimental and control groups. In the experimental group, orthodontic force of 1 N was first applied, then direct occlusal forces of 3 and 10 N were applied on each opposite tooth. While in the control group, occlusal forces were applied without orthodontic treatment. The tooth displacement, the stress state in the PDL and the directions of the resultant forces on each tooth were evaluated. Results: In the case of molars ligated, the maximum hydrostatic stress in the molars' PDL decreases by 60%. When an initial tooth displacement of several microns occurs in response to an orthodontic force, the direction of the occlusal force changes simultaneously. Even a moderate occlusal force (3 N per tooth) can almost completely offset the mesial forces on the maxillary teeth, thus to provide effective anchorage effect for the orthodontics. Conclusions: The proposed method is effective for simulating ligation and direct occlusion. Figure-of-eight ligature can effectively disperse orthodontic forces on the posterior teeth, while a good original occlusal relationship provides considerable anchorage effects in orthodontics. Graphical abstract: Image, graphical abstract